Answer:
ne solution was found :
r = -2
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
8*(x+6)-10+r-(3*(x+12)+5*x)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(((8•(x+6))-10)+r)-(3•(x+12)+5x) = 0
Step 2 :
Equation at the end of step 2 :
((8 • (x + 6) - 10) + r) - (8x + 36) = 0
Step 3 :
Equation at the end of step 3 :
r + 2 = 0
Step 4 :
Solving a Single Variable Equation :
4.1 Solve : r+2 = 0
Subtract 2 from both sides of the equation :
r = -2
One solution was found :
r = -2
Explanation: